STRATEGIC FRAMEWORK OF SYSTEMIC INTERDEPENDENCE DEVELOPMENT IN HIGH-TECH SECTORS: CLUSTER-NETWORK APPROACH - O.Yu. Kudrina; V.A. Omelyanenko (Економіка та право)
In current conditions the national security increasingly depends on the processes of development and transfer of high techno logies that affect the level of its socio-economic development and are determined by the effectiveness of identifying innovative priorities and developing an international strategy. This necessitates the development of theoretical foundations and practical recommendations on the participation of countries in the processes of development of high technologies in the global innovation system, taking into account national security and development strategy. The article is devoted to the analysis of peculiarities of high-tech sectors development and the features of innovative linkages between them. The conceptual bases of creating clusters in high-tech sectors based on the system integration approach are proposed and the main advantages of this approach are determined. An algorithm for determining the development options for certain inter-branch clusters, taking into account the international component of national security, has been developed. It is proved, that Ukraine needs to create clustered network structures in order to integrate into the world of innovation space, expand its development and attract new technologies. In this case the fundamental objectives of intersectoral clusters development of on a network basis were identified. In was shown, that the effectiveness of high-tech industries development in order to achieve international competitiveness and national security can be ensured through the use of tools for stimulating interactions (accounting and analytical support, marketing) and an evolutionary strategy, that involves the development of intersectoral relationships based on international clusters, that evolve under globalization in a virtual form for the selection of organizational and technological resources and their integration through information technology.